The Politics of Trafficking : the First International Movement to Combat the Sexual Exploitation of Women. - Limoncelli, Stephanie (Stanford University Press, 2010)
This work reveals how the first international movement to combat the traffic in women struggled to achieve its goal of protecting women due to conflicts among reformers and the presumed necessity of women's sexual labor for nation-state and empire-bui.